Simulasi Algoritma Monte Carlo Dalam Memprediksi Tingkat Hafalan Al-Qur’an Santri - M, Mutia; Nurcahyo, Gunadi Widi; Yunus, Yuhandri (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
Islamic boarding schools are known to be able to give birth to the Qur'an's tahfidz. With the memorization program, the halaqah about the basic text of the religion makes the Islamic boarding schools increasingly known to the community as an educational institution and a strong milestone of religious knowledge that can bring blessings. The purpose of this study was to predict the level of rote learning of the students at the Tahfiz Lan Tabur Pagaralam Islamic Boarding School. Thus, it is easier for Islamic boarding schools to take strategies to improve the quality of students themselves. The data processed in this study are data sourced from the Natural Boarding School of Tahfiz Al-Qur’an Lan Tabur Pagaralam. Based on the number of students who memorized the Al-Qur'an or Tahfidz in the 2017 to 2019 class which is processed by Monte Carlo algorithm simulation. The processing step is to bring up a random number from the sampling data that has been taken. The results of testing on this method found that the system used to predict the level of memorization of the Al-Qur'an with an average accuracy of 84% in 2018 and an average accuracy of 88% in 2019. With a high degree of accuracy, simulations performed using the Monte Carlo algorithm can predict the number of students memorized by the Qur'an, making it easier for Islamic boarding schools to obtain information about the likelihood of future events at the level of memorization of students at Islamic boarding schools Alam Tahfiz Al-Qur’an Lan Tabur Pagaralam.